2016
DOI: 10.1021/acs.jpcc.6b04980
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Stability of One-Dimensional Pore ZSM-22 Zeolite in Hot Water

Abstract: The hydrothermal stability of 1-D medium pore zeolites ZSM-22 with different nominal Si/Al ratios (30, 46, 80, and 100) was investigated in hot liquid water environments at different temperatures (100, 150, 200, and 250 °C) and different exposure times (6, 12, 36, 72, and 144 h). The changes in the zeolite structure, phase transformation, and textural properties were characterized by X-ray diffraction, scanning electron microscopy, 27Al and 29Si magic-angle spinning nuclear magnetic resonance, temperature-prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
(94 reference statements)
4
11
0
Order By: Relevance
“…The XRD patterns of the zeolite ZSM-22 material and ZSM-22/PES membranes are shown in Figure 1a,b, respectively. As shown in Figure 1a, the XRD pattern of ZSM-22 crystal sample exhibits characteristic peaks of a Theta-1 (TON) topology of ZSM-22 material, which is in agreement with the database of zeolite structures as reported in the literature [57,58]. This material presents five peaks at 2θ values of 8.18°, 20.30°, 24.20°, 24.52° and 25.59°, respectively, corresponding to the ZSM-22 structure [59,60].…”
Section: Xrd Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…The XRD patterns of the zeolite ZSM-22 material and ZSM-22/PES membranes are shown in Figure 1a,b, respectively. As shown in Figure 1a, the XRD pattern of ZSM-22 crystal sample exhibits characteristic peaks of a Theta-1 (TON) topology of ZSM-22 material, which is in agreement with the database of zeolite structures as reported in the literature [57,58]. This material presents five peaks at 2θ values of 8.18°, 20.30°, 24.20°, 24.52° and 25.59°, respectively, corresponding to the ZSM-22 structure [59,60].…”
Section: Xrd Analysissupporting
confidence: 88%
“…The obtained ZSM-22 zeolite material was then directly incorporated into the pristine PES casting solution, resulting in a series of composite membranes containing ZSM-22. It is observed that the XRD patterns of ZSM-22/PES membranes with to 0 wt.% loadings exhibit a mainly amorphous phase with one broad characteristic peak of a typical PES phase (Figure 1b As shown in Figure 1a, the XRD pattern of ZSM-22 crystal sample exhibits characteristic peaks of a Theta-1 (TON) topology of ZSM-22 material, which is in agreement with the database of zeolite structures as reported in the literature [57,58] [59,60]. This is indicative of the successful synthesis of the highly crystalline ZSM-22 material when using TEOS as silica source at 160 • C for 144 h with an Si/Al ratio of 60.…”
Section: Xrd Analysissupporting
confidence: 87%
“…[ 86 ] A similar observation was made for TON zeolite, with a 1D channel system, exposed to HLW. At T = 373–473 K, only mild desilication was observed and no extra‐framework Al species were detected after > 72 h. [ 87 ] At T = 523 K, aluminum atoms started to leach during HLW treatment and formation of extra‐framework Al was observed; thus formed EFAL deposits served as a protective environment, limiting the further removal of silicon atoms. Increased mobility of aluminum, which was observed for prolonged time in the presence of water resulted in aluminum reinsertion into the framework.…”
Section: Reactive Interaction Of Water With Zeolitesmentioning
confidence: 99%
“…The most stable catalyst was cerium modified MTT. Stability of TON, another medium pore zeolite with one-dimensional pore architectures was reported by (Jamil et al, 2016).…”
Section: Perspective On Glycerol Over Hierarchical Zeolites In the Prmentioning
confidence: 77%